The Effect of Talking Chips Model Containing Science Literacy on Students’ Learning Competencies In the Material of Climate Change and Its Impact on Ecosystems at Junior High School 20 Padang - Wa Ode Nurhawa; Relsas Yogica; Indra Hartanto; Syamsurizal Syamsurizal (ATRIUM PENDIDIKAN BIOLOGI, 2019)
The research problem at Junior High School 20 Padang  is that the learning model used has not varied, the low competency of students from the aspects of knowledge, attitudes, and skills as well as the implementation of learning models with science literacy. The efforts that can be done are applying the talking chips model with science literacy to the students at Junior High School 20 Padang on the material of climate change and its impact for the ecosystem. The purpose of this research is to find out The Effect of Talking Chips model containing science literacy on students’ learning competencies in the material of climate change and its impact on ecosystems at Junior High School 20 Padang. This research is quasi-experimental research with design randomized control-group posttest only design. The population used was all class VII students’ of Junior High School 20  Padang 2018/2019. Sampling was done using the cluster sampling technique, we selected VII.2 as experimental class and class VII.7 as control class. Based on the results of the students' competency knowledge research  tcount 2.85 > ttable 1.67, the competency attitudes tcount 1.78 > ttable 1.67, and the skills competency tcount 1.78 > ttable 1.67. It showed the hypothesis is accepted. Application of the talking chips model containing science literacy can improve the competencies of class VII students of Junior High School 20 Padang.